Cultural Transformation in the Development of Home Industries in Karanganyar Regency, Central Java, Indonesia - Lestari Eny (EDP Sciences, 2021)
The development of home industries based on cultural values is one of the strategies used by the Indonesian government to alleviate poverty in rural communities. In the development of home industries, a model of cultural transformation based on local wisdom offers opportunities for communities to show their local identity and local potential as well as displaying their own uniqueness. The goal of this research is to discover how the transformation of local culture based on local wisdom takes place in the development of home industries in rural communities. The research method is qualitative and uses a case study approach which examines the shift in cultural values and the importance of local wisdom in the development of home industries. In this case study, the data collection includes various sources, such as observation, interviews, FGDs, audio visual material, documents, and reports. The research results show that the development of home industries in rural areas is full of dynamics in the cultural transformation from an agrarian culture to an industrial culture. This cultural transformation has a multiplier effect and acts as a trigger and determining factor in rural development.